Absence of genetic differentiation in the coral Pocillopora verrucosa along environmental gradients of the Saudi Arabian Red Sea - Robitzch, Vanessa; Banguera-Hinestroza, Eulalia; Sawall, Yvonne; Al-Sofyani, Abdulmohsin; Voolstra, Christian R. (Frontiers in Marine Science, 2015)
The Red Sea is the world’s northernmost tropical sea. The 2,000 km long, but narrow basin creates distinct environmental conditions along its latitudinal spread. The Red Sea displays a pronounced salinity gradient from 41 to 37 PSU (north to south) with an opposing temperature gradient from 21-27°C in the north to 27-33.8°C in the south. The Red Sea further displays a decreasing nutrient gradient from south to north that can also influence underwater light fields due to higher phytoplankton content and turbidity. Despite this strong variation in temperature, salinity, nutrients, and light conditions, the Red Sea supports large and diverse coral reef ecosystems along its nearly entire coastline. Only few studies have targeted whether these prevailing gradients affect genetic connectivity of reef organisms in the Red Sea. In this study, we sampled the abundant reef-building coral Pocillopora verrucosa from ten reefs along a latitudinal gradient in the Red Sea covering an area of more than 850 km. We used nine Pocillopora microsatellite markers to assess the underlying population genetic structure and effective population size. To assure the exclusion of cryptic species, all analyzed specimens were chosen from a single mitochondrial lineage. Despite large distances between sampled regions covering pronounced, but smooth temperature and salinity gradients, no significant genetic population structure was found. Rather, our data indicate panmixia and considerable gene flow among regions. The absence of population subdivision driven by environmental factors and over large geographic distances suggests efficient larval dispersal and successful settlement of recruits from a wide range of reef sites. It also advocates, broadcast spawning as the main reproductive strategy of Pocillopora verrucosa in the Red Sea as reflected by the absence of clones in sampled colonies. These factors might explain the success of Pocillopora species throughout the Indo-Pacific and Arabian Seas.